Using Social Innovation as a Theoretical Framework to Guide Future Thinking on Facilitating Collaboration Between Mental Health and Criminal Justice Services - Hean, Sarah; Willumsen, Elisabeth; Ødegård, Atle; Bjørkly, Stål (International Journal of Forensic Mental Health, 2015)
Offender mental health is a major societal challenge. Improved collaboration between mental health and criminal justice services is required to address this challenge. This article explores social innovation as a conceptual framework with which to view these collaborations and develop theoretically informed strategies to optimize interorganizational working. Two key innovation frameworks are applied to the offender mental health field and practice illustrations provided of where new innovations in collaboration, and specifically co-creation between the mental health system and criminal justice system, take place. The article recommends the development of a competency framework for leaders and front line staff in the mental health system and criminal justice systems to raise awareness and skills in the innovation process, especially through co-creation across organizational boundaries.
Keywords: Co-création; Collaboration; Criminologie; Innovation sociale; Justice; Réservé UdeM; Santé

Using Social Innovation as a Theoretical Framework to Guide Future Thinking on Facilitating Collaboration Between Mental Health and Criminal Justice Services - Hean, Sarah; Willumsen, Elisabeth; Ødegård, Atle; Bjørkly, Stål (International Journal of Forensic Mental Health, 2015)
Offender mental health is a major societal challenge. Improved collaboration between mental health and criminal justice services is required to address this challenge. This article explores social innovation as a conceptual framework with which to view these collaborations and develop theoretically informed strategies to optimize interorganizational working. Two key innovation frameworks are applied to the offender mental health field and practice illustrations provided of where new innovations in collaboration, and specifically co-creation between the mental health system and criminal justice system, take place. The article recommends the development of a competency framework for leaders and front line staff in the mental health system and criminal justice systems to raise awareness and skills in the innovation process, especially through co-creation across organizational boundaries.
Number: 4
Keywords: Co-création; Collaboration; Criminologie; Innovation sociale; Justice; Réservé UdeM; Santé